Influencing factors of residents' environmental health literacy in Shaanxi province, China: a cross-sectional study - Yan Zhao; Yun Sheng; Jieting Zhou; Hao Wang; Mumba Mulutula Chilufya; Xuan Liu; Alaa Osman Mohamed; Jing Han; Chengjuan Qu (BMC, 2022)
Abstract Background This study comprehensively analyzed the basic conditions and influencing factors of the residents' environmental health literacy (EHL) level in Shaanxi Province, China in 2020, and provided a scientific basis for exploring new ideas and new methods to improve the EHL level of the whole people. Methods In the cross-sectional study with a multi-stage random sampling method, 1320 participants were recruited in 6 neighborhood committees (administrative villages) from the Shaanxi province of China between 15-69 years old. The Core Questions for Assessment of EHL of Chinese Citizens (Trial Implementation) was adopted to measure the EHL of the respondents. Results The survey showed the level of EHL of residents is 17.6% in Shaanxi in 2020. Among them, the basic concepts, basic knowledge, and basic skills classification literacy levels are 34.7%, 6.89%, and 37.95% respectively. The EHL ratio of rural residents is significantly lower than that of urban residents (12.38 vs. 29.02%). A noticeable difference was shown in various aspects and environmental health issues of EHL between urban and rural populations. Conclusions Many factors are affecting the level of EHL. Education and science popularization of basic environmental and health knowledge in key areas and populations should be strengthened, and behavioral interventions should be carried out according to the characteristics of the population.